Differential effects of high-fat diet on salivary and gut microbiota - Bai, Jingxuan; Tian, Yixue; Lu, Yujia; Chen, Yuke; Yu, Min; Gao, Xuemei (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesMicroorganisms contribute to the pathogenesis of obesity, while more studies focus on gut microbiome. However, the relationship between oral microbiota and obesity has yet to be elucidated. This study was designed to investigate the similarities and differences in the effects of a high-fat diet on salivary and gut microbiota through mouse experiments, exploring the hypothesis that oral microbial mechanisms may contribute to obesity.MethodsAn obese mouse model was established in male C57BL/6J mice by feeding a high-fat diet, confirmed by body weight records and blood glucose tests. This study evaluated the physiological effects of the high-fat diet on mice. 16S rRNA sequencing technology was used to analyze changes in salivary and gut microbiota, and gas chromatography-mass spectrometry was employed to evaluate 17 short-chain and medium-chain fatty acids quantitatively.ResultsThe microbiota distribution in salivary was different between the high-fat diet (HFD) and normal chow diet (NCD) groups. At the genus level of salivary microbiota, Streptococcus and Escherichia were highly abundant in the HFD group. Rodentibacter and Turicibacter were more abundant in the NCD group. Regarding the gut microbiome, the diversity changes of gut microbiota are more significant than those of salivary microbiota. The HFD group had a significantly higher abundance of Kineothrix, Cryptobacteroides, and a lower abundance of CAG-485. Nine genera had consistent alterations in salivary and gut microbiota, among which Akkermansia, Lactobacillus, and Intestinimonas were significantly correlated with physiological indicators, and Muribaculum was significantly correlated with increased decanoic acid levels in the HFD group. The dysregulated nine genera were associated with significant upregulation of certain metabolic pathways of the HFD group, including the pentose phosphate, bacterial invasion of epithelial cells, and steroid biosynthesis pathways.ConclusionsThere are differences and similarities in the effects of HFD on salivary and gut microbiota. Certain genera of the oral-gut axis altered consistently by HFD may affect obesity through mechanisms involving metabolic pathways and inflammation.